Numerical control granulator for biomass fuel - LIU ZHIHE (2018)
The utility model discloses a numerical control granulator for biomass fuel, including the frame with fix the casing in the frame, be provided with transport portion and granulation portion in the casing, transport portion and granulation portion all follow transversal arrangement, the horizontal position of transport portion will be higher than granulation portion, still installs the electricallycontrolled device who is used for controlling transport portion and the work of granulation portion in the frame. The utility model discloses the biomass fuel granulation of producing has hollow structure, makes the biomass fuel granulation and the area of contact of air increase to electrically controlled device can control the density of biomass fuel granulation, thereby has improved biomass fuel's combustion efficiency. 本实用新型公开了种生物质燃料用数控造粒机，包括机架和固定在机架上的壳体，壳体内设置有输送部与造粒部,输送部与造粒部均沿横向布置，输送部的水平位置要高于造粒部，机架上还安装有用于控制输送部与造粒部工作的电控装置。本实用新型生产出的生物质燃料造粒，具有中空的结构，使生物质燃料造粒与空气的接触面积增大，并且电控装置可以对生物质燃料造粒的密度进行控制，从而提高了生物质燃料的燃烧效率。